Knowledge Diffusion from Academia to Industry - Lin, Bou‐Wen; Shih, Hui‐Yu; Chang, Yu‐Yu (British journal of management, 2025)
Universities and firms serve as key agents in the creation and transfer of knowledge, where universities primarily develop fundamental knowledge, which is later transferred across institutional boundaries and evolves into different forms for either scientific advancement or economic value creation. Although much research has examined technology transfer, the mechanisms influencing the speed and continuity of knowledge diffusion remain underexplored. Drawing upon institutional theory, this study investigates the speed and continuity of knowledge transfer from universities’ scientific outputs to patented technologies utilized by industry stakeholders. This paper disentangles the multi‐level and cross‐boundary dynamics of university–industry knowledge diffusion by examining the bridging role of science‐linked patents (SLPs). Based on a longitudinal analysis of scientometric data, we find that universities’ academic reputations and the standard shaping of SLPs accelerate the speed of knowledge diffusion. Interestingly, academic reputation does not directly influence the long‐term industrial impact of scientific knowledge. Additionally, contextual similarity between universities and patentees, as well as patents’ boundary‐spanning activities, are found to reduce the speed of knowledge diffusion and diminish the subsequent industrial impact of scientific knowledge. Our findings underscore that the early emergence of SLPs is critical to the impact of scientific discoveries on the trajectory of subsequent technological innovations.